2000
DOI: 10.1099/0022-1317-49-4-355
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Shigella sonnei isolated from three well-documented outbreaks in school children

Abstract: Fifty-eight isolates of Shigella sonnei from three outbreaks in school children and eight control isolates from epidemiologically unrelated sporadic clinical infections in Taiwan were compared by antibiotic susceptibility testing and molecular typing. Antibiotic susceptibility testing showed that all strains except one sporadic isolate were multi-resistant. Ribotyping after restriction endonuclease digestion with SalI, PvuII and HindII generated the same ribosomal pattern in 65 of the 66 isolates. Plasmid prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Tacket and colleagues investigated the plasmid profile of 10 S. sonnei isolates and found 10 different patterns (19). In other studies, 61 S. sonnei strains resulted in identification of 42 distinct plasmid patterns (20). These studies may suggest the existence of a large number of different plasmids in the S. sonnei populations.…”
Section: Discussionmentioning
confidence: 93%
“…Tacket and colleagues investigated the plasmid profile of 10 S. sonnei isolates and found 10 different patterns (19). In other studies, 61 S. sonnei strains resulted in identification of 42 distinct plasmid patterns (20). These studies may suggest the existence of a large number of different plasmids in the S. sonnei populations.…”
Section: Discussionmentioning
confidence: 93%
“…Within a single outbreak, strains had identical antibiogram patterns. Thus, the identification of the new and unusual pattern of antimicrobial resistance among isolates cultured from multiple patients is often the first indication of epidemic spread (Lee et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates with resistant phenotypes RIII, RIV and RV each had a distinct NotI and XbaI-PFPs. PFGE 100 90 80 70 60 50 40 30 PFGE 40·00 50·00 60·00 80·00 100·00 120·00 140·00 160·00 180·00 200·00 220·00 240·00 300·00 350·00 400·00 450·00 500·00 600·00 700·00 800·00 RVI RVI RVI RVI RVI RVI RVI RVI RVI RVI RVI RVI RVI RVII RVI RVI RVI RVI RVI RI RVIII RVIII $ $ RI RI RI RI RIII RI RI RI RI RI $ RI RI RIV RII RII $ RI RI RI RI RI Multi-resistance to the antimicrobial agents used in treatment of shigellosis has been reported in many parts of the world (Ling et al 1988;Ashkenazi et al 1995;Lee et al 2000;Jeong et al 2003;Lee and Puthucheary 2003). In this study, a high resistance rate to streptomycin was observed in 100 95 90 85 80 75 70 65 60...…”
Section: Pulse-field Gel Electrophoresismentioning
confidence: 99%
“…Salmonella infection, known as salmonellosis, induces vomiting, diarrhoea, fever and abdominal cramps and can last several days. Outbreaks of YESS group-associated diseases are common (Tacket et al 1985;Mahon et al 1997;Lee et al 2000;Varma et al 2003), and consequently at the time of writing, this group of prokaryotes is the most extensively sampled in genome sequencing projects, making it useful to illustrate the points we wish to make.…”
Section: Introductionmentioning
confidence: 99%